Ward identities, B -> V transition form factors and applications - Paracha, M. Ali; El-Bennich, Bruno [UNESP]; Aslam, M. Jamil; Ahmed, Ishtiaq; IOP (Iop Publishing Ltd, 2015)
Long distance effects are studied in the rare exclusive semileptonic B(d,s) -> V l(+)l(-) decays, where V denotes a K* or phi meson. The form factors, which describe the meson transition amplitudes in the effective Hamiltonian approach, are calculated by means of Ward identities, experimental constraints and extrapolated within a general vector meson dominance framework. These form factors are then compared to the ones obtained in Lattice QCD simulations, with Light Cone Sum Rules and a Dyson-Schwinger equation approach. Additionally, the B-d -> K*l(+)l(-) and B-s -> phi l(+)l(-) branching ratios are computed and the differential branching fractions are given as a function of the squared-momentum transfer.